CHAOS-BASED SIMULTANEOUS DATA COMPRESSION AND ENCRYPTION - USAMA, MUHAMMAD (2018)
Various compression and encryption tools are in existence, and they are characteristically applied in sequence, i.e., compression followed by encryption or encryption followed by compression. This requires the output of one operation be piped to the other leading to a potentially complicated and time-consuming process. Consequently, many simultaneous data compression and encryption mechanisms have been proposed to address these issues.